ISSUES OF REGIONAL DEVELOPMENT OF SMALL BUSINESS - Rashidov, Rahmatullo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Entrepreneurial activity is of particular importance for the development of the national economy. This article provides detailed information on the characteristics of entrepreneurial activity in the context of the transition to the innovative economy.